Rekonstruksi Epistemologi Rasionalisme René Descartes dalam Perspektif Filsafat Hindu tentang Hakikat Pengetahuan Di Indonesia - Faishal, Muhammad (Jurnal Penelitian Agama Hindu, 2025)
René Descartes’ rationalism emphasizes reason as the primary source of truth through the method of systematic doubt and the principle of cogito ergo sum (“I think, therefore I am”). This approach serves as a fundamental basis for constructing modern knowledge systems that are logical and structured. In contrast, Hindu philosophy offers an alternative view, emphasizing intuitive experience, inner consciousness, and scriptural authority as epistemological foundations. In the context of Indonesia’s growing openness to cross-cultural philosophical dialogue, there is a need to integrate these two approaches to address contemporary challenges of knowledge that are not only rational but also existential and spiritual. This study aims to reconstruct Descartes’ epistemology of rationalism through the lens of Hindu philosophy in order to provide a more holistic understanding of the nature of knowledge. Using a qualitative method with a literature review approach, this research examines Descartes’ works alongside key Hindu philosophical texts such as the Upanishads and Bhagavad Gita. The findings reveal that while Descartes’ rationalism offers a systematic foundation for epistemology, it is limited in addressing the transcendental dimensions of knowledge. Hindu philosophy complements these limitations by presenting knowledge as a path of inner realization and spiritual insight. Therefore, this reconstruction contributes to the development of a more integrative epistemological framework in Indonesia bridging Western rationalism and Eastern wisdom traditions.